HUBUNGAN ANTARA KONSELING ASI EKSKLUSIF PADA IBU HAMIL TRIMESTER III DENGAN PEMBERIAN ASI EKSKLUSIF DI KECAMATAN ARJASA KABUPATEN JEMBER - Khusnul Khotimah; IGA Ayu Karnasih; Zidny Yuris Yuhbaba (Jurnal Kesehatan dr. Soebandi, 2016)
Mother's milk (ASI) is the best food a baby at the early age of life. Exclusive breastfeeding means that the infant receives only breast milk. Although exclusive breastfeeding is so important, but not all mothers do. In Jember coverage of exclusive breastfeeding at 66.37% while achieving the target of 80% is one Arjasa districts. Based on the obtained results of the survey 60% of mothers do not exclusively breastfeed their infants. The purpose of this study was to analyze the relationship between counseling in third trimester pregnant women with exclusive breastfeeding in the Arjasa district of Jember 2014. This type of research is the correlation. The population in this study was all the third trimester pregnant women gestational age> 36 weeks in the Arjasa district of Jember 2014 amounted to 63 people. The sample size in this study are 54 people with the sampling technique used is random sampling. Data analyzed using a computer with the Statistical Product and Service Solutions (SPSS) 16.0 for Windows. The results of the frequency distribution of the respondents obtained the result that most of the third trimester maternal age was 22-27 years (64.8%), secondary education (51.9%). Mothers who receive counseling are largely exclusive breastfeeding in infants for 24 hours ie (74.04%), mothers were not given counseling on exclusive breastfeeding in infants for 24 hours ie (33.33%). Based on chi square x2 values ​​obtained count (9012)> x2 tables (3,481), with a significance value of 0.003> 0.05, so that there is a relationship between the provision of counseling with a third trimester pregnant women exclusively breastfeeding babies for 24 hours. While the value of contingency coefficient of 0.378, meaning that the relationship is at a low or weak category is uncertain. The conclusion of this research there is a relationship between exclusive breastfeeding in mothers who were counseled by the closeness of the relationship is at a low or weak category is uncertain